Restaurants that work : case studies of the best in the industry - Dorf, Martin E. (New York : Whitney Library of Design, 1992)
Restaurants That Work presents a complete run-down on how successful restaurateurs, teaming up with architects and designers, ply their craft. It answers the questions: How does a freshman restaurateur without any prior experience decide what type of restaurant to open? Where should it be located? Who is the potential customer and competition? What type of food should be offered, and at what price? What should the restaurant look like?" "Martin E. Dorf has created an essential sourcebook for restaurateurs, consultants, and design professionals. Restaurants That Work presents 18 in-depth case studies of such successful restaurants as Scoozi, Union Square Cafe, and Chinois, along with personal interviews with their owners, chefs, architects, designers, kitchen planners, and consultants. The book explores all the ingredients that contribute to the success of a restaurant, including concept and menu development, site selection, space planning and design, construction costs, kitchen planning, staff selection, and management techniques. In addition, the book features invaluable information on building codes, utility requirements, and construction costs analysis, as well as a special appendix on handicapped access laws."--BOOK JACKET.
Includes bibliographical references (p. 219) and index.
Also issued online.
Keywords: Restaurant management -- Case studies; Restaurants -- Design and construction